2015
DOI: 10.1186/s13014-015-0376-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gated treatment using an optical surface imaging and gating system on an Elekta linac

Abstract: BackgroundKnowing the technical characteristics of gated radiotherapy equipment is crucial for ensuring precise and accurate treatment when using techniques such as Deep-Inspiration Breath-Hold and gating under free breathing. With one of the first installations of the novel surface imaging system Catalyst™ (C-RAD AB, Sweden) in connection with an Elekta Synergy linear accelerator (Elekta AB, Sweden) via the Elekta Response Interface, characteristics like dose delivery accuracy and time delay were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 20 publications
1
50
0
4
Order By: Relevance
“…In the case of systems which do not use triode guns, rather long beam on/off latencies have been observed. 28 The current system would likely exhibit similar latencyhowever, it is worth noting that the same criticism can be made of currently proposed MRI-Linac systems, which appear to be using diode rather than triode guns at this stage. There have also been triode based RF guns proposed-such a structure may be able to improve the system latency to that achievable with DC triode guns.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of systems which do not use triode guns, rather long beam on/off latencies have been observed. 28 The current system would likely exhibit similar latencyhowever, it is worth noting that the same criticism can be made of currently proposed MRI-Linac systems, which appear to be using diode rather than triode guns at this stage. There have also been triode based RF guns proposed-such a structure may be able to improve the system latency to that achievable with DC triode guns.…”
Section: Discussionmentioning
confidence: 99%
“…Hardware latency causes a delay between a beam on signal and the commencement of radiation delivery, and vice versa for beam off. Previous studies have found beam‐on delays ranging between 220 ms18 and nearly 1 s 17. This raises questions about the dosimetric consequences of gating an Elekta linac during free breathing.…”
Section: Discussionmentioning
confidence: 97%
“…A separate set of experiments was carried out to investigate whether the depth signal from a Kinect v2 system could be used to gate an Elekta linac via the previously tested Elekta Response ™ gating interface 16, 17. See Fig.…”
Section: Methodsmentioning
confidence: 99%
“…On linear accelerators which use diode guns, beam gating must be carried out by radiofrequency (RF) pulse interruption methods, and this appears to result in quite long beam on/off latency. 9,10 Triode guns are also important for treatment machines which provide multiple treatment energies, and both photon and electron treatment modes. This is because both the target heating and the dose rate are correlated with the product of beam current and beam energy.…”
Section: Introductionmentioning
confidence: 99%